Kekerasan: Wujud Kehampaan EksistensiSebuah Tinjauan Etis atas Pemikiran Erich Fromm - Kasdin Sihotang (Respons: Jurnal Etika Sosial, 2009)
Erich Fromm’s analysis of the root of violence in The Anatomy of HumanDestructiveness can be seen as a starting point to understand the nature of violence. He contendsthat violence is not existential but exists as a result of a negative condition that prohibits someoneto grow according to his own choice. According to this definition, human aggression is neutral. Itcan be identified as defensive if it is used to save life, and as destructive one if it destroys the lifeitself and against the human values. Fromm explains that the progress of technology and scienceare the main factors that cause modern man, that is called cybernetic man, to act destructively intheir life.